Low-chromium magnesite-chrome brick with high high-temperature breaking strength and preparation method of low-chromium magnesite-chrome brick
By regulating the raw material formula and process flow, combined with the use of lime milk and nano yttrium oxide, the problem of insufficient flexural strength of magnesium-chromium bricks at high temperature of 1850℃ is solved, and the high temperature flexural strength is improved and the chromium content is reduced. Environmental protection and performance requirements.
Patent Information
- Application Number
- CN202411764123.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-18
AI Technical Summary
The existing magnesium-chromium bricks cannot meet the high-temperature flexural strength in 1850℃ high-temperature tunnel kilns, and the high chromium content does not meet the environmental protection requirements.
By reasonably matching raw materials, adjusting the CaO/SiO2 ratio, introducing lime milk and nano yttrium oxide, improving the production process, and improving the high-temperature flexural strength of the products.
The high-temperature flexural strength of magnesium chromium bricks at high temperature of 1850℃ has been achieved to reach 5.5-6.5MPa, reducing the chromium content and improving the environmental protection of the products.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of refractory materials, and in particular relates to a magnesia-chrome brick with low chromium, high temperature and high flexural strength and a preparation method thereof. Background Art
[0002] The materials used in ultra-high temperature tunnel kilns and ultra-high temperature tunnel kiln firing zones are generally fused and bonded magnesia-chromium and directly bonded magnesia-chromium materials, with a chromium content of about 9%-18%. Due to the high temperature of the high temperature tunnel kiln firing zone, the material selection needs to withstand high temperature, thermal stress, load, rapid temperature changes and the impact of flue gas flow. Magnesia-chrome bricks have excellent load softening temperature, thermal shock stability and high temperature performance, which can meet the use requirements of tunnel kilns at 1800℃ and below, but in high temperature tunnel kilns at 1850℃ and above, their high temperature performance is limited, especially the high temperature flexural strength does not meet the use requirements.
[0003] At present, magnesia-chrome bricks for high-temperature tunnel kilns are generally made of high-purity magnesia sand, chrome concentrate, and fused magnesia-chrome sand as raw materials, which are mixed and pressed in a certain proportion, and then dried and sintered at high temperature. Because of the impurity SiO2 introduced into the raw materials, the product generates a silicate phase in the matrix, which surrounds the membrane or shell of the periclase crystal, resulting in a low degree of direct bonding between crystals. The high-temperature performance of the product is poor, especially the high-temperature flexural strength is low. It is easy to deform, fall off, and peel off during high-temperature use, thus affecting the service life. In addition, the green development of refractory materials requires the chromium content to be as low as possible. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that the existing magnesia-chrome bricks cannot meet the high-temperature flexural strength requirements in a high-temperature tunnel kiln fired at 1850°C. By reasonably matching raw materials, regulating the raw material CaO / SiO2, improving the production process and formula, and improving the high-temperature flexural strength of the product, a green and environmentally friendly low-chromium magnesia-chrome brick with high high-temperature flexural strength and a preparation method thereof are provided.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A low-chromium, high-temperature flexural strength magnesia-chrome brick, the raw materials of which are: fused magnesia particles, fused magnesia fine powder, high-purity magnesia particles, chrome concentrate particles, chrome concentrate fine powder, high-purity magnesia fine powder, nano yttrium oxide, an additional binder and lime milk.
[0006] The weight proportions of the raw materials added in the present invention are: 40-50 parts of fused magnesia particles, 25-29 parts of fused magnesia fine powder, 8-10 parts of chromium concentrate particles, 4-6 parts of chromium concentrate fine powder, 5-15 parts of high-purity magnesia particles, 1-2 parts of nano yttrium oxide, 2-3% of the total weight of the raw materials added in a binder, and 3-4% of the total weight of the raw materials added in a lime milk.
[0007] The fused magnesia particles have a particle size of 5-2 mm and 2-0 mm, or a combination of the two; The fused magnesia fine powder has a particle size of ≤0.088 mm; The particle size of the high-purity magnesia particles is one of 4-3 mm and 3-1 mm or a combination of the two; The particle size of the chromium concentrate particles is ≤1 mm; The particle size of the chromium concentrate fine powder is ≤0.088 mm; The particle size of the nano yttrium oxide is 10-20nm; The binder is one or a combination of dextrin liquid, dextrin dry powder, water and magnesium chloride aqueous solution.
[0008] The preparation method of the low-chromium, high-temperature flexural strength magnesia-chrome brick of the present invention is as follows: Step 1: Pretreatment process Put the fused magnesia particles, chrome concentrate particles and high-purity magnesia particles into a sand mixer according to the above proportions, add lime milk, and mix for 2-3 minutes to obtain a pretreated material; Step 2: Wet milling process Put the fused magnesia fine powder, chromium concentrate fine powder and nano yttrium oxide into a wet mill according to the above proportion, then put them into the pretreated material obtained in step 1, and then add a binder. After wet milling for 8-12 minutes, the mud material is milled; Step 3: Forming and drying process The mixed clay is pressed into shape by a machine and then dried in a drying kiln at a temperature of 60-150°C for 24-48 hours; Step 4: Coating process The dried bricks are evenly coated with nano yttrium oxide to fully cover the surface of the bricks. After coating, the bricks are loaded according to the parts; Step 5: Firing process The assembled products enter into a 1780-1820℃ high temperature tunnel kiln and are fired for 103-118 hours in a weak oxidizing atmosphere. The excess air coefficient is controlled at 1.02-1.20. They are kept at 1750-1780℃ for 4-8 hours. After exiting the firing zone, they are slowly cooled to room temperature for 44-55 hours to obtain low-chromium magnesia-chrome bricks with high high-temperature flexural strength.
[0009] By combining particles of different sizes, the raw materials are stacked as closely as possible, and the binder is added twice to evenly wrap the fine powder around the aggregate, making the distribution of each component more even.
[0010] The fused magnesia particles are combined with high-purity magnesia particles as aggregates, taking into account the economy of the product. At the same time, the fused magnesia is smelted at high temperature, and the periclase grains are coarser than those of the general sintered magnesia, and the degree of direct bonding between the crystals is high. At the same time, the M-Cr spinel and M-Fe spinel generated by the chrome concentrate and magnesia are evenly distributed in the periclase crystal film. After the fired product is cooled, the periclase crystal film disappears, and the M-Cr spinel and M-Fe spinel are directly combined with the periclase crystal, which improves the load softening temperature, high temperature flexural strength and thermal shock stability of the product.
[0011] Lime milk is introduced to adjust the CaO / SiO2 ratio in the fused magnesia to be greater than 2. During the firing process, the Ca(OH)2 in the lime milk first reacts with the SiO2 in the fused magnesia to generate 2CaO·SiO2 and 3CaO·SiO2, thus blocking the formation of low-melting-point phases CMS and M2S formed by impurities during the high-temperature firing of magnesia and chromium concentrate.
[0012] Through the pretreatment in step one, the lime milk and nano-yttrium oxide are evenly wrapped on the outside of the granular material. During the high-temperature firing process, the periclase crystals gradually grow and directly combine with each other to form a 2CaO·SiO2-3CaO·SiO2-Y2O3 composite crystal phase at the periclase grain boundary. The whiskers of these crystal phases are intertwined with each other, which improves the degree of bonding between the periclase crystals and achieves the effect of improving the high-temperature load softening temperature and high-temperature flexural resistance of the product.
[0013] Nano yttrium oxide is introduced as a coating material. During the high-temperature firing process, part of the impurity SiO2 in the magnesia and chrome concentrate reacts with the lime milk, and the other part reacts with the surface-coated nano yttrium oxide to generate Y2Si2O7, which penetrates into the gaps between periclase, M-Cr spinel and M-Fe spinel, playing a secondary protective role. At the same time, it also improves the bonding degree between the crystals, further improving the high-temperature flexural strength of the product. The high-temperature flexural strength of the product reaches 5.5-6.5MPa at 1850℃.
[0014] The beneficial effects of the present invention are: The process of the invention is simple, and a product with good performance can be prepared, the chromium content in the product is reduced, and the product is made more environmentally friendly while maintaining the original advantages. By adding lime milk, dicalcium sand and nano yttrium oxide and improving the production process, CaO / SiO2 in the fused magnesia is adjusted, the generation of low melting point phases CMS and M2S is reduced to a great extent, and the high temperature flexural strength, high temperature load softening temperature and thermal shock stability of the product are improved, so that the high temperature flexural strength of the product at 1850°C reaches 5.5-6.5MPa. DETAILED DESCRIPTION
[0015] The following examples illustrate the implementation and features of the present invention, but the present invention is not limited to the following embodiments.
[0016] Embodiment 1:
[0017] The preparation method of the low-chromium, high-temperature flexural strength magnesia-chrome brick of the present invention is as follows: Step 1: Pretreatment process 30 parts of fused magnesia particles with a particle size of 5-2mm, 20 parts of fused magnesia particles with a particle size of 2-0mm, 10 parts of chrome concentrate particles with a particle size of ≤1mm, 5 parts of high-purity magnesia particles with a particle size of 4-3mm and lime milk accounting for 4% of the total weight of the original material are put into a sand mixer according to the above proportions, and mixed for 2 minutes to obtain a pre-treated material; Step 2: Wet milling process Put 1 part of nano yttrium oxide with a particle size of 10-20nm, 29 parts of fused magnesia fine powder with a particle size of ≤0.088mm and 5 parts of chromium concentrate fine powder with a particle size of ≤0.088mm into a wet mill according to the above proportions, then put the pretreated material obtained in step 1 and dextrin liquid accounting for 2% of the total weight of the original material into the wet mill, and wet mill for 10 minutes before the mud material is milled; Step 3: Forming and drying process The mixed clay is pressed into shape by a machine and then dried in a drying kiln at 60°C for 48 hours; Step 4: Coating process The dried bricks are evenly coated with nano yttrium oxide with a particle size of 10-20nm, so that the nano yttrium oxide fully covers the surface of the bricks, and after coating, they are loaded according to the parts; Step 5: Firing process The assembled products enter a 1780℃ high-temperature tunnel kiln and are fired for 103 hours in a weakly oxidizing atmosphere. The excess air coefficient is controlled at 1.02 and the product is kept at 1750℃ for 4 hours. After exiting the firing zone, the product is slowly cooled to room temperature for 44 hours to obtain a low-chromium magnesia-chrome brick with high high-temperature flexural strength.
[0018] Embodiment 2:
[0019] The preparation method of the low-chromium, high-temperature flexural strength magnesia-chrome brick of the present invention is as follows: Step 1: Pretreatment process 28 parts of fused magnesia particles with a particle size of 2-0mm, 17 parts of fused magnesia particles with a particle size of 2-0mm, 10 parts of chrome concentrate particles with a particle size of ≤1mm, 5 parts of high-purity magnesia particles with a particle size of 4-3mm, 5 parts of high-purity magnesia with a particle size of 3-1mm and 3.5% of lime milk accounting for the total weight of the original material are put into a sand mixer, and mixed for 2 minutes to obtain a pre-treated material; Step 2: Wet milling process Put 1 part of nano yttrium oxide with a particle size of 10-20nm, 29 parts of fused magnesia fine powder with a particle size of ≤0.088mm and 5 parts of chromium concentrate fine powder with a particle size of ≤0.088mm into a wet mill according to the above proportions, then put the pretreated material obtained in step 1 and a magnesium chloride aqueous solution accounting for 2.5% of the total weight of the original material into the wet mill, and wet mill for 12 minutes before the mud material is milled; Step 3: Forming and drying process The mixed clay is pressed into shape by a machine and then dried in a drying kiln at 100°C for 36 hours; Step 4: Coating process The dried bricks are evenly coated with nano yttrium oxide with a particle size of 10-20nm, so that the nano yttrium oxide fully covers the surface of the bricks, and after coating, they are loaded according to the parts; Step 5: Firing process The assembled products enter into a 1800℃ high temperature tunnel kiln and are fired for 110 hours in a weak oxidizing atmosphere. The excess air coefficient is controlled at 1.10. They are kept at 1770℃ for 6 hours. After exiting the firing zone, they are slowly cooled to room temperature for 50 hours to obtain low-chromium magnesia-chrome bricks with high high temperature flexural strength.
[0020] Embodiment 3:
[0021] The preparation method of the low-chromium, high-temperature flexural strength magnesia-chrome brick of the present invention is as follows: Step 1: Pretreatment process 25 parts of fused magnesia particles with a particle size of 5-2mm, 15 parts of fused magnesia particles with a particle size of 2-0mm, 10 parts of high-purity magnesia particles with a particle size of 4-3mm, 5 parts of high-purity magnesia with a particle size of 3-1mm, 10 parts of chrome concentrate particles with a particle size of ≤1mm and lime milk accounting for 3% of the total weight of the original material are put into a sand mixer, and mixed for 3 minutes to obtain a pre-treated material; Step 2: Wet milling process Put 2 parts of 10-20nm nano yttrium oxide, 28 parts of fused magnesia fine powder with a particle size of ≤0.088mm and 5 parts of chromium concentrate fine powder with a particle size of ≤0.088mm into a wet mill according to the above proportions, and then put the pretreated material obtained in step 1 and a binder accounting for 3% of the total weight of the original material, the binder is a mixture of dextrin dry powder and water, the mixing ratio is 1:1, and the mud material is milled after wet milling for 8 minutes; Step 3: Forming and drying process The mixed clay is pressed into shape by a machine and then dried in a drying kiln at 150°C for 24 hours; Step 4: Coating process The dried bricks are evenly coated with nano yttrium oxide with a particle size of 10-20nm, so that the nano yttrium oxide fully covers the surface of the bricks, and after coating, they are loaded according to the parts; Step 5: Firing process The assembled products enter into a 1780℃ high temperature tunnel kiln and are fired for 103 hours in a weak oxidizing atmosphere. The excess air coefficient is controlled at 1.02. The products are kept at 1780℃ for 8 hours. After exiting the firing zone, they are slowly cooled to room temperature for 55 hours to obtain low-chromium magnesia-chrome bricks with high high temperature flexural strength.
[0022] Comparative Example 1: Step 1: Add 85 parts of high-purity magnesia particles and fine powder, 15 parts of chromium concentrate particles and fine powder into a sand mixer according to the ratio, and then add 4 parts of dextrin liquid and mix for 15 minutes to obtain a mud material; Step 2: After the clay obtained in step 1 is pressed into shape by a machine, it is dried in a drying kiln at a temperature of 60-150°C for 24 hours and then loaded into trucks according to the parts; Step 3: The assembled products are placed in a tunnel kiln and fired at 1680°C for 6 hours to obtain magnesia-chrome bricks.
[0023] Table 1 Performance test data of the products obtained in Examples 1-3 and Comparative Example 1
Claims
1. A low-chromium, high-temperature flexural strength magnesia-chrome brick, characterized by: The weight proportions of the raw materials added are: 40-50 parts of fused magnesia particles, 25-29 parts of fused magnesia fine powder, 8-10 parts of chromium concentrate particles, 4-6 parts of chromium concentrate fine powder, 5-15 parts of high-purity magnesia particles, 1-2 parts of nano yttrium oxide, the amount of binder added is 2-3% of the total weight of the raw materials, and the amount of lime milk added is 3-4% of the total weight of the raw materials.
2. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: The particle size of the fused magnesia particles is one of 5-2 mm and 2-0 mm or a mixture of the two.
3. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1 is characterized by: The fused magnesia fine powder has a particle size of ≤0.088 mm.
4. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: The particle size of the high-purity magnesia sand particles is one of 4-3 mm and 3-1 mm or a mixture of the two.
5. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: The particle size of the chromium concentrate particles is ≤1 mm.
6. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: The particle size of the chromium concentrate fine powder is ≤0.088 mm.
7. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: The particle size of the nano yttrium oxide is 10-20nm.
8. The low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: The binder is one or a combination of dextrin liquid, dextrin dry powder, water and magnesium chloride aqueous solution.
9. The method for preparing a low-chromium, high-temperature flexural strength magnesia-chrome brick according to claim 1, characterized in that: Step 1: Pretreatment process Put the fused magnesia particles, chrome concentrate particles and high-purity magnesia particles into a sand mixer according to the above proportions, add lime milk, and mix for 2-3 minutes to obtain a pretreated material; Step 2: Wet milling process Put the fused magnesia fine powder, chromium concentrate fine powder and nano yttrium oxide into a wet mill according to the above proportion, then put them into the pretreated material obtained in step 1, and then add a binder. After wet milling for 8-12 minutes, the mud material is milled; Step 3: Forming and drying process The mixed clay is pressed into shape by a machine and then dried in a drying kiln at a temperature of 60-150°C for 24-48 hours; Step 4: Coating process The dried bricks are evenly coated with nano yttrium oxide to fully cover the surface of the bricks. After coating, the bricks are loaded according to the parts; Step 5: Firing process The assembled products enter into a 1780-1820℃ high temperature tunnel kiln and are fired for 103-118 hours in a weak oxidizing atmosphere. The excess air coefficient is controlled at 1.02-1.
20. They are kept at 1750-1780℃ for 4-8 hours. After exiting the firing zone, they are slowly cooled to room temperature for 44-55 hours to obtain low-chromium magnesia-chrome bricks with high high-temperature flexural strength.
Citation Information
Cited By
Low-chromium high-performance magnesite-chrome brick and preparation method thereof
CN122541213A